Peran Pembelajaran Berbasis Internet dalam Meningkatkan Keterampilan Membaca Pemahaman Siswa Sekolah Dasar - Atikah Mumpuni (Jurnal Ilmiah Wahana Pendidikan, 2023)
Internet access is currently very easy to obtain, but the use of the internet has not been maximized, especially in learning activities. Internet-based learning that has been carried out in elementary schools has not been comprehensive. This makes students not maximally seek, view, and utilize sources, thus making students' reading comprehension skills not so honed. This research is a type of literature review research which has four stages, namely exploration, visualization, identification, and verification. The results showed that internet-based learning actually played a role in improving students' reading comprehension skills. This is because there are online texts that students often read, thereby supporting their reading comprehension skills.